Translation of the satter’s division of responsibility in feeding questionnaire into Brazilian Portuguese : a cross-sectional study - Sousa, Rafaella Dusi de (2023)
This cross-sectional study aimed to translate and perform a psychometric analysis (eval- uation of reproducibility and internal consistency) of the sDOR.2-6y ™ into Brazilian Portuguese. The translation and back-translation followed the protocol required by the NEEDs Center, and the approved version was called “sDOR.2-6y™—Português-Brasil”. The approved version was submitted to a test–retest round to verify its reproducibility through the Intraclass Correlation Coeffi- cient (ICC). A pilot study was performed to assess the internal consistency of the instrument. The reproducibility analysis (n = 23) showed a total ICC of 0.945. With the data from the pilot study (n = 384), the internal consistency evaluation was analyzed through Cronbach’s alpha coefficient, and the instrument obtained an overall Cronbach’s alpha of 0.301. The translation of the sDOR.2-6y ™ into Brazilian Portuguese is the first and only tool available for the Brazilian population to exclusively assess the division of responsibility in feeding, which is essential to the academic community, health professionals, and research on child feeding. Therefore, this instrument in Brazilian Portuguese will allow future research on the division of responsibility in feeding among those responsible for children in Brazil.